A novel bioengineered derivative of nisin displays enhanced antimicrobial activity against clinical Streptococcus agalactiae isolates. (December 2019) - Hayes, K.; Field, D.; Hill, C.; O'Halloran, F.; Cotter, L.
Highlights: Some activity was detected for wild-type nisin against the majority of S. agalactiae isolates. A novel derivative, nisin PV, displayed improved activity against 64.8% of isolates. A gene encoding the nisin resistance protein was detected in 98.4% of isolates. There is potential for use of nisin and its derivatives in the treatment of S. agalactiae infections. Abstract: Objectives: Streptococcus agalactiae is the leading cause of neonatal disease worldwide, and infections caused by this opportunistic pathogen are becoming increasingly more prevalent in adults. With the global incidence of antimicrobial resistance continuing to rise, there is a recognised need for new therapeutic agents. Nisin is a potent antimicrobial peptide with demonstrated broad-spectrum activity against a range of clinically significant pathogens. This study aimed to examine the efficacy of nisin against a clinical population of S. agalactiae isolates and further to investigate the bioactivity of a novel bioengineered derivative of the peptide, designated nisin PV. Methods: A deferred antagonism assay was used to assess the bioactivity of wild-type nisin and nisin PV against 122 S. agalactiae isolates. Minimum inhibitory concentrations (MICs) were evaluated to determine the specific activity of both peptides. The genetic basis of nisin resistance among the isolate collection was investigated by PCR detection of the nsr gene. Results: In total, 91.0% (111/122) of the collection showed some level of susceptibility to nisin, whilst 9.0% (11/122) displayed complete resistance. Interestingly, the nisin derivative exhibited enhanced antimicrobial activity for 64.8% of the isolates. The frequency of the nsr gene conferring nisin resistance was 98.4% (120/122), suggesting that resistance may be linked to levels of expression of the protein or other regulatory elements. Conclusion: This study indicates that there is potential for the use of nisin and its derivatives as therapeutic agents against S. agalactiae infections.